Good night, beloved - Christophers, Harry 1953-; Naylor, Edward W. 1867-1934; Davies, Peter Maxwell 1934-2016; MacMillan, James 1959-; Chilcott, Bob; Pinsuti, Ciro 1829-1888; Cornysh, William -1523; Todd, Will 1970-; Stanford, Charles Villiers 1852-1924; Cornysh, William -1523; Whitacre, Eric 1970-; Williams, Roderick; et al. (Coro Records, 2021)
What could be more welcome than a little repose and respite from the demands of daily life? This beautiful album features a stunning selection of music spanning over 500 years. From exuberant early works such as Hoyda, hoyda, jolly rutterkin and I am a jolly foster to the sublime Whisper Him my name, Lullabye for Lucy, Stanford's glorious The Blue Bird, and a new commission from Roderick Williams, this is truly music to escape to
Compact disc
Title from disc surface
Program and performer notes, English texts and Latin texts with English translation (27 pages) inserted in container
Keywords: Choruses, Sacred (Mixed voices); Choruses, Secular (Mixed voices); Sacred vocal music; Sacred music